Sosialisasi UMKM Go Digital: Solusi Cerdas Kembangkan Usaha di Era Digital - Afiifah, Zera Nurfajrina (Universitas Muhammadiyah Surakarta, 2025)
The UMKM Go Digital socialization program is a strategic step to encourage the development of micro, small, and medium enterprises (UMKM) in the digital era. The digital economy in Indonesia continues to grow alongside global digital transformation. Through digital marketing socialization, introduction to e-commerce, and training in logo, banner, and packaging creation conducted by the KKN Mas 2024 Group 37 team, this research aims to enhance the effectiveness and efficiency of UMKM marketing by utilizing online payment systems and digital technology. The methods used include field visits and practical training for UMKM owners. The research findings reveal that the training effectively enhanced UMKM owners' comprehension and abilities in business branding. With continued assistance from the academic community, it is anticipated that UMKM will adapt more effectively to market demands and boost their profitability.